Changes in Journalism during the state of alarm in Spain: The use of video in El País - García Chamizo, Fernando; Carrero Márquez, Oliver (Estudios sobre el Mensaje Periodístico, 2021)
This study is focused on the main changes in journalistic practices occurred during the first wave of the COVID in Spain, from April to June, 2020. The case observed in ‘El País ‘on-line edition newspaper demonstrates some paradigmatic transformations in the way information is delivered to the public and consumed by them, both formal and content-related. It explains not only the new role of journalists, but also the role of audiovisual information in this digital newspaper, by analysing the quality of the content, the structure, as well as the compliance with the deontological codes inherent to the quality of the newspaper's information product. In essence, this article dissects the decisions and work of journalists and managers at a crucial time for ‘El País‘, the audience and society, within the new journalistic panorama in Spain.
Keywords: challenges of online journalism; new journalistic roles; deontology; COVID treatment in El País Digital; transmedia journalism